2022
DOI: 10.21608/edj.2022.130667.2048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Firing on the Color, Translucency, and Flexural Strength of Newly Introduced Lithium Disilicate Ceramics

Abstract: Statement of problem:Ceramic is subjected to multiple firing which exposed it to more heat treatments. The effect of these heat treatments on optical and mechanical properties of lithium disilicate glass-ceramics is not fully studied.Objective: To evaluate the Impact of multiple firings cycles on color change, translucency, and flexural strength of lithium disilicate ceramic fabricated by press and milled technology.Material and Methods: Lithium disilicate ceramics fabricated by two methods were used. Sixty di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The reduction in translucency in this study as a result of repeated firing was in agreement with previously conducted studies [ 19 , 27 ] whose findings were credited to the alteration in crystal size and/or orientation. Also, another study reported an initial increase in translucency with an increased number of firings followed by a decrease in the translucency with increasing the number of sintering cycles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The reduction in translucency in this study as a result of repeated firing was in agreement with previously conducted studies [ 19 , 27 ] whose findings were credited to the alteration in crystal size and/or orientation. Also, another study reported an initial increase in translucency with an increased number of firings followed by a decrease in the translucency with increasing the number of sintering cycles.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study [ 19 ] investigated the effect of multiple firings on zirconia-reinforced glass ceramics, both pressed and machined (Vita Amberia, VITA Zahnfabrik, Germany). They found that multiple firings caused a significant decrease in biaxial flexure strength when it was fired up to 5 times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation